SP2.1.3 Effect of laparoscopic sleeve gastrectomy on vasoactivemediators in obese hypertensive patients: A prospective study. (9th August 2022) - Salman, Mohamed; Noureldin, Khaled; Issa, Mohamed; Badawi, Marwa; Tourky, Mohamed
Abstract: Introduction: The relationship between obesity and high blood pressure is established; however, detailed pathways for such association are still under research. This work aims to assess the changes in neprilysin, vasoconstrictor and vasodilatory molecules in obese hypertensive patients undergoing laparoscopic sleeve gastrectomy (LSG). Patients: Prospective study was done on 59 hypertensive obese patients in whom LGS was performed. Blood pressure, as well as blood samples for neprilysin, angiotensinogen, angiotensin II, renin, endothelin-1 "ET-1", aldosterone, atrial natriuretic peptide "ANP" and B-type natriuretic peptide "BNP", were assessed before and 15 months after surgery. Patients were divided into two groups according to the remission of hypertension (HTN). Results: After 15 months, remission of hypertension was seen in 42 patients (71%). The declines in the following measurements were higher in patients with remission than those with persistent HTN: aldosterone (p = .029567), angiotensin II (p < .000001), angiotensinogen (p = .000021), n eprilysin (p = .000601), renin(p = .000454) and endothelin-1(p = .000030). There was a significantly higher incrementin ANP (p = .000002) a nd a n on-significant increment i n B NP (p = .081740).Angiotensin II 15 months after LSG and Δ ANP % were significant independent predictors of persistent HTN. Conclusion: In setting of LSG, aldosterone, angiotensinogen, angiotensin II, renin and neprilysin were significantly lower in patients with remission of HTN after 15 months than those with persistent HTN, and natriuretic peptides were significantly higher. lower postoperative level of angiotensin II and a larger percentage increment of ANP are independently associated with hypertension remission after LSG.